Pengaruh Kearifan Pangan Lokal Suku Rejang terhadap Penanganan Stunting Baduta di Bengkulu Utara - Danur Azissah Roesliana Sofais; Berlian Kando Sianipar; Darmawansyah Darmawansyah (Jurnal Keperawatan Silampari, 2019)
The purpose of this research is to identify the effect of local food wisdom of Rejang trait to treat stunting infant at North Bengkulu. The design of this research is using queasy-experiments study, one group of stunting babies (height-for-age z-score < -2) consists 36 respondents with 12-24 months old. The result of this research shows that there is a change on stunting infant height after weaning treatment with mean score pre-test: 69.61 and mean for post-test: 77.16. correlation score >0.05 (0.846). It means that giving weaning treatment for stunting infant by using local food wisdom is positive. It can increase height gradually. Keywords: Local Food, Treatment, Stunting